2007
DOI: 10.1002/iub.14
|View full text |Cite
|
Sign up to set email alerts
|

First evidence for an LDL‐ and HDL‐associated nitratase activity that denitrates albumin‐bound nitrotyrosine—Physiological consequences

Abstract: SummaryIn the systemic circulation, LDL occurs in the form of a weakly nitrated LDL-albumin complex (LAC). The question here is whether LAC (or HDL) is able to denitrate the albumin-bound 3-NO 2 -tyrosine (3NT). Nitrated albumin was incubated in the presence of lipoprotein fraction (LPF) to be tested, with or without Ca 21 . After precipitation and centrifugation, supernatants (SNs) and protein pellets (PP) were collected. HCl proteolysis was carried out with deuterated 3NT as an internal standard, and amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
(53 reference statements)
3
19
0
Order By: Relevance
“…However, under inflammatory conditions, xanthine oxidoreductase is expressed leading to detrimentally reduce O 2 and NO 3 -into O 2 ÅÀ and Å NO that in turn may interact, reconstituting the ONOO -pool. As a whole, LDL and HDL are able to denitrate the HSA Tyr-3-NO 2 residues (Khan et al, 1997;Léger et al, 2008).…”
Section: Tyr Nitrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under inflammatory conditions, xanthine oxidoreductase is expressed leading to detrimentally reduce O 2 and NO 3 -into O 2 ÅÀ and Å NO that in turn may interact, reconstituting the ONOO -pool. As a whole, LDL and HDL are able to denitrate the HSA Tyr-3-NO 2 residues (Khan et al, 1997;Léger et al, 2008).…”
Section: Tyr Nitrationmentioning
confidence: 99%
“…Remarkably, 82% of NO in blood ($7 lM) is transported as a S-nitrosothiol bound at the HSA residue Cys34 (Peters, 1996). Additionally, HSA could bind NO at Trp and Tyr residue(s) (Khan et al, 1997;Yamakura and Ikeda, 2006;Léger et al, 2008).…”
Section: Human Serum Albumin Nitrosylation and Nitrationmentioning
confidence: 99%
“…We have recently established that free albumin (i.e. albumin which is not associated with LDL) once nitrated by PN to form the 3‐NO 2 ‐Tyr residues can be denitrated by a specific protein structure belonging to lipoprotein edifices [LDL and high density lipoprotein (HDL)] [6]. It was observed that the highest nitrase activity is associated to LDL.…”
Section: Introductionmentioning
confidence: 99%
“…This is further confirmed by the fact that at D4, PNA levels are similar in normoglycemic and ETH infants. Whether nitroalbumin is denitrated or cleared through increased transendothelial transport [42] remains to be determined, although Leger et al [43] recently reported that nitroalbumin can be denitrated by plasma lipoproteins. We and others have reported earlier that cytosolic [44,45] and mitochondrial [46] proteins are denitrated in cellulo within minutes.…”
Section: Increased Peroxynitrite Production Is An Early and Transientmentioning
confidence: 99%